Factors Influencing Sleep Difficulty and Sleep Quantity in the Citizen Pscientist Psoriatic Cohort - Mary Patricia Smith; Karen Ly; Quinn Thibodeaux; Thulasi Weerasinghe; Kristen Beck; Lindsey Shankle; April W. Armstrong; Marc Boas; Alisha Bridges; Frank Doris; Joel M. Gelfand; Brian Lafoy; et al. (Adis, Springer Healthcare, 2019)
Abstract Introduction Sleep is essential for overall health and well-being, yet more than one-third of adults report inadequate sleep. The prevalence is higher among people with psoriasis, with up to 85.4% of the psoriatic population reporting sleep disruption. Poor sleep among psoriasis patients is particularly concerning because psoriasis is independently associated with many of the same comorbidities as sleep dysfunction, including cardiovascular disease, obesity, and depression. Given the high prevalence and serious consequences of disordered sleep in psoriasis, it is vital to understand the nature of sleep disturbance in this population. This study was designed to help meet this need by using survey data from Citizen Pscientist, an online patient portal developed by the National Psoriasis Foundation. Methods Our analysis included 3118 participants who identified as having a diagnosis by a physician of psoriasis alone or psoriasis with psoriatic arthritis. Demographic information, psoriasis severity and duration, sleep apnea status, smoking and alcohol consumption, itch timing, and sleep characteristics were included. Two separate multivariate logistic regression models in STATA were used to determine whether the presence of psoriatic arthritis, age, gender, body mass index, comorbid sleep apnea, psoriasis severity, timing of worst itch, smoking status, or high-risk alcohol consumption were associated with sleep difficulty or low sleep quantity, defined by the American Academy of Sleep Medicine as less than 7 h of sleep per night on average. Results Results from the multivariate logistic regressions found that sleep difficulty was associated with psoriatic arthritis (OR 2.15, 95% CI [1.79-2.58]), female gender (2.03 [1.67-2.46]), obese body mass index (BMI ≥ 30) (1.25 [1.00-1.56]), sleep apnea (1.41 [1.07-1.86]), psoriasis severity of moderate (1.59 [1.30-1.94]) or severe (2.40 [1.87-3.08]), and smoking (1.60 [1.26-2.02]). Low sleep quantity was associated with obese BMI (1.62 [1.29-2.03]), sleep apnea (1.30 [1.01-1.68]), psoriasis severity of moderate (1.41 [1.16-1.72]) or severe (1.40 [1.11-1.76]), and smoking (1.62 [1.31-2.00]). Sleep difficulty and low sleep quantity were not associated with age, alcohol consumption, or timing of worst itch. Conclusion These results are potentially meaningful in several aspects. We identify an important distinction between sleep difficulty and sleep quantity in psoriatic disease, whereby having psoriatic arthritis and being female are each associated with sleep difficulty despite no association with low sleep quantity. Furthermore, there is conflicting evidence from prior studies as to whether psoriasis severity is associated with sleep difficulty, but this well-powered, large study revealed a strong, graded relationship between psoriasis severity and both sleep difficulty and low sleep quantity. Overall, our results show that both sleep difficulty and low sleep quantity were associated with multiple factors in this analysis of a large psoriatic cohort. These findings suggest that dermatologists may gather clinically useful information by screening psoriatic patients for trouble sleeping and low sleep quantity to identify potential comorbidities and to more effectively guide disease management.